2005
DOI: 10.1007/s00438-005-0004-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and analysis of sequences showing sex-specific cytosine methylation in the mealybug Planococcus lilacinus

Abstract: Genomic libraries of Planococcus lilacinus, a mealybug in which paternal chromosomes are facultatively heterochromatic and inactive in sons but not in daughters, were probed with subtraction probes in order to estimate the number of sequences displaying sex-specific cytosine methylation in CpG dinucleotides. Sequences showing male-specific methylation were found to occur approximately 2.5 times more often than those showing female-specific methylation. In order to directly isolate sequences showing sex-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Some species dominantly display methylation in the context of CpG, such as C. intestinalis , S. gregaria , B. mori , M. extradentata and A. mellifera [5,9,14,47,48,50], while other species such as P. lilacinus and D. melanogaster, Pogonomyrmex barbatus display a high proportion of methylation in non-CpG methylation sites [10,13,51]. The bisulfite sequencing analysis performed in our study identified only methylation of CpG sites, suggesting that this is the dominant type of DNA methylation in B. glabrata .…”
Section: Discussionmentioning
confidence: 99%
“…Some species dominantly display methylation in the context of CpG, such as C. intestinalis , S. gregaria , B. mori , M. extradentata and A. mellifera [5,9,14,47,48,50], while other species such as P. lilacinus and D. melanogaster, Pogonomyrmex barbatus display a high proportion of methylation in non-CpG methylation sites [10,13,51]. The bisulfite sequencing analysis performed in our study identified only methylation of CpG sites, suggesting that this is the dominant type of DNA methylation in B. glabrata .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Drosophila shows mainly methylation in a CpT or CpA context [27] . In the mealy bug Planococcus lilacinus , methylcytosine appears to occur nearly independently of the identity of the 3â€Č nucleotide [28] , [29] . Thus, the sequence context of Medauroidea DNA methylation seems to be more similar to that of vertebrates than to that of mealy bugs or Drosophila.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of unusual methylation like 6mA, 7mG and 5mC and non-CpG methylation was reported in P. lilacinus [Deobagkar et al, 1982;Achwal et al, 1983]. Hypermethylation of genomic DNA in males in Pseudococcus obscurus and Pseudococcus calceolariae was reported by Scarbrough et al [1984] and enrichment of CpG methylation in males of P. lilacinus was demonstrated by Mohan et al [2005], while Bongiorni et al [1999] found hypomethylation in the paternal set in P. citri . Thus there are contradicting reports on differential methylation of DNA between males and females in mealybugs.…”
mentioning
confidence: 94%